A Novel ATM Gene Mutation Affecting Splicing in an Ataxia-Telangiectasia Patient - GÜNEY, AHMET İLTER; BARIŞ, SAFA (KARGER, 2022)
Ataxia-telangiectasia (AT) is an autosomal recessive disorder characterized by progressive ataxia, choreoathetosis and immunodeficiency beginning in early childhood. An 8-year-old girl was referred with a diagnosis of AT. She had gait disturbance and dysarthria for 3years. Multiple cutaneous telangiectases were observed on her face, trunk and limbs. Sequence analysis of the ATM gene revealed a homozygous c.7308-15A>G mutation in IVS49. Human Splicing Finder predicted that the mutation could activate an intronic cryptic acceptor site. We designed primers for amplification of related exons (48-50) from cDNA for evaluating splicing pattern. Sequencing of ATM exons 48-50 revealed a 14-nucleotide insertion from intron 49, between exons 49 and 50, resulting in premature termination of translation at codon 2439. To conclude, we report a novel mutation in a classical AT case, which resulted in an alternatively spliced transcript and was predicted to form a truncated protein or null protein due to nonsense-mediated decay.
Keywords: ATM; Ataxia-telengiectasia syndrome; Splicing mutation; Novel mutation; cDNA sequencing; IDENTIFICATION